Perilaku Adaptif dan Sikap Moderat Guru dan Dosen Pendidikan Agama Islam - Sari Narulita (Universitas Negeri Jakarta, 2023)
This study analyses the influence of cross-cultural adaptive behaviour and the moderate attitude of IRE lecturers and teachers. Moderation is essential amidst the rise of thoughts that lead to violence in the name of religion. This study uses a Quantitative Approach with the regression method. The population in this study were Islamic Religious Education lecturers and teachers, with 153 respondents. The data collection technique used a questionnaire with data analysis using the SPSS version 29 program. The results showed no difference in the adaptive behaviour level across cultures and moderate attitudes by profession. Meanwhile, based on gender, affiliation and age, differences were found in some of the variable indicators in this study. This study also shows the influence of cross-cultural adaptive behaviour of 41.3% on moderate attitudes. This research shows the importance of developing cross-cultural adaptive behaviour to increase moderation for Islamic Religious Education lecturers and teachers.